Working hours, common mental disorder and suicidal ideation among junior doctors in Australia: a cross-sectional survey - Allison Milner; Anthony D LaMontagne; Helen Christensen; Samuel B Harvey; Benjamin G Veness; Katherine Petrie; Joanna Crawford; Jessica Dean (BMJ Open, 2020)
Objective Despite concern regarding high rates of mental illness and suicide amongst the medical profession, the link between working hours and doctors’ mental health remains unclear. This study examines the relationship between average weekly working hours and junior doctors’ (JDs’) mental health in Australia.Design and participants A randomly selected sample of 42 942 Australian doctors were invited to take part in an anonymous Beyondblue National Mental Health Survey in 2013, of whom 12 252 doctors provided valid data (response rate approximately 27%). The sample of interest comprised 2706 full-time graduate medical trainees in various specialties, at either intern, prevocational or vocational training stage. Consultants and retired doctors were excluded.Outcome measures Main outcomes of interest were caseness of common mental disorder (CMD) (assessed using a cut-off of 4 as a threshold on total General Health Questionnaire-28 score), presence of suicidal ideation (SI) (assessed with a single item) and average weekly working hours. Logistic regression modelling was used to account for the impact of age, gender, stage of training, location of work, specialty, marital status and whether JDs had trained outside Australia.Results JDs reported working an average of 50.1 hours per week (SD=13.4). JDs who worked over 55 hours a week were more than twice as likely to report CMD (adjusted OR=2.05; 95% CI 1.62 to 2.59, p<0.001) and SI (adjusted OR=2.00; 95% CI 1.42 to 2.81, p<0.001) compared to those working 40–44 hours per week.Conclusions Our results show that around one in four JDs are currently working hours that are associated with a doubling of their risk of common mental health problems and SI. These findings suggest that management of working hours represents an important focus for workplaces to improve the mental health of medical trainees.